PENGARUH PENGGUNAAN PODCASTING TERHADAP KETERAMPILAN BERBICARA PADA MATA PELAJARAN BAHASA INDONESIA SISWA SANGGAR BIMNINGAN KAMPUNG BHARU MALAYSIA - Ginting, Tassya Rahmayanti; Saragih, Mandra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using podcasting on the srudents speaking ability in Bahasa Indonesia subjects at Sanggar Bimbingan Kampung Bharu Malaysia. The research method used is quantitative pre-experimental with a pretest-posttest one group design. The sampling technique in this study used a purpose sampling technique. The instrument used was a speaking ability observation sheet. Result the research found showed of the hypothesis test obtained a sig value. (2-tailed) 0.000 <0.005 then Ho is rejected and Ha is accepted, so it can be concluded that the use of podcasting has an effect on speaking ability in Bahasa Indonesia subjects of Sanggar Bimbingan Kampung Bharu Malaysia students. Based on the phenomenon that occurred, the use of podcasting is highly recommended to be used in Bahasa Indonesia subjects.